From Head to Toe - Carle, Eric ([New York], 1997)
Encourages the reader to exercise by following the movements of various animals; presented in a question and answer format.
Keywords: Questions and answers; Physical fitness; Exercise; Exercise; Physical fitness; Juvenile literature; Juvenile literature